2002
DOI: 10.1159/000065816
|View full text |Cite
|
Sign up to set email alerts
|

Open Eye Injuries in the Pediatric Population in Kuwait

Abstract: Objective: To report the epidemiological characteristics of pediatric open globe injuries and to discuss treatment, management and outcomes of such injuries. Materials and Method: The hospital records and operative notes of 95 patients 16 years old and younger who were treated for open eye injury at Ibn Sina Hospital, Kuwait between September 1995 and January 1999 were reviewed. The average age of patients was 6.6 years. Patients were divided into three groups according to their final visual acuity (FVA): grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
2
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 15 publications
4
17
2
4
Order By: Relevance
“…It was also reported that game-related accidents were the most common cause of pediatric OGIs. Consistent with the literature, in 58.3% of cases, game-related accidents were found to be responsible for the OGI in our study (6)(7)(8)(9). The most common causative objects of the injuries were glass and pencil in this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It was also reported that game-related accidents were the most common cause of pediatric OGIs. Consistent with the literature, in 58.3% of cases, game-related accidents were found to be responsible for the OGI in our study (6)(7)(8)(9). The most common causative objects of the injuries were glass and pencil in this study.…”
Section: Discussionsupporting
confidence: 91%
“…The results of the studies regarding which eye is more commonly affected in OGIs suggests that pediatric OGI affects both eyes at similar rates (1,7,8,12,13). In our study, we showed only a slight difference between the right and left eyes.…”
Section: Discussioncontrasting
confidence: 50%
“…2,18,82,146 Overall, less than 5% of eye injuries in children are caused by animals. 13,38,40,57,80,90,96,108,118,124,133,144 Eye injuries caused by insects, predominantly ophthalmomyiasis, are the most widely reported. Dogs are the animals most likely to cause adnexal injuries in children, with a predilection for canalicular injury.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent inflammation was more prominent in patients who had previous surgery for trauma. 8,9 When the ocular medium appeared hazy due to inflammation of the anterior vitreous, a capsulectomy and vitrectomy were performed via an anterior-pars plana route.…”
Section: Methodsmentioning
confidence: 99%